Dietary selection of distinct gastrointestinal microorganisms drives fiber utilization dynamics in goats - Xiaoli Zhang; Rongzhen Zhong; Jian Wu; Zhiliang Tan; Jinzhen Jiao (Microbiome)
Abstract Background Dietary fiber is crucial to animal productivity and health, and its dynamic utilization process is shaped by the gastrointestinal microorganisms in ruminants. However, we lack a holistic understanding of the metabolic interactions and mediators of intestinal microbes under different fiber component interventions compared with that of their rumen counterparts. Here, we applied nutritional, amplicon, metagenomic, and metabolomic approaches to compare characteristic microbiome and metabolic strategies using goat models with fast-fermentation fiber (FF) and slow-fermentation fiber (SF) dietary interventions from a whole gastrointestinal perspective. Results The SF diet selected fibrolytic bacteria Fibrobacter and Ruminococcus spp. and enriched for genes encoding for xylosidase, endoglucanase, and galactosidase in the rumen and cecum to enhance cellulose and hemicellulose utilization, which might be mediated by the enhanced microbial ATP production and cobalamin biosynthesis potentials in the rumen. The FF diet favors pectin-degrading bacteria Prevotella spp. and enriched for genes encoding for pectases (PL1, GH28, and CE8) to improve animal growth. Subsequent SCFA patterns and metabolic pathways unveiled the favor of acetate production in the rumen and butyrate production in the cecum for SF goats. Metagenomic binning verified this distinct selection of gastrointestinal microorganisms and metabolic pathways of different fiber types (fiber content and polysaccharide chemistry). Conclusions These findings provide novel insights into the key metabolic pathways and distinctive mechanisms through which dietary fiber types benefit the host animals from the whole gastrointestinal perspective. Video Abstract